A participação dos contingentes do Exército Brasileiro na missão de estabilização das Nações Unidas no Haiti (Minustah) - Lessa, Marco Aurélio Gaspar (2007)
This work aims to study the Brazilian Army as an actor in the process of implementation of public policies. This study evaluates and verifies, in loco, if the actions executed by the Brazilian Army contingent in Haiti (MINUSTAH), especially the Brazilian Battalion, are effectively contributing to satisfactory security conditions for the development and reestablishment of Haiti's institutional normality. The main activities developed by the six Brazilian contingents that had already acted and are still acting in Haiti will be described. This work ratifies the Brazilian Army's contribution to the creation of a favorable environment so that the Haitian State, with the contribution of other countries, international organisms and non-governmental organizations, could work on its reconstruction.